"Salivary gland cellular architecture in the Asian malaria vector mosquito Anopheles stephensi". Issue 1 (December 2015) - Wells, Michael; Andrew, Deborah
Abstract Background Anopheles mosquitoes are vectors for malaria, a disease with continued grave outcomes for human health. Transmission of malaria from mosquitoes to humans occurs by parasite passage through the salivary glands (SGs). Previous studies of mosquito SG architecture have been limited in scope and detail. Methods We developed a simple, optimized protocol for fluorescence staining using dyes and/or antibodies to interrogate cellular architecture inAnopheles stephensi adult SGs. We used common biological dyes, antibodies to well-conserved structural and organellar markers, and antibodies againstAnopheles salivary proteins to visualize many individual SGs at high resolution by confocal microscopy. Results These analyses confirmed morphological features previously described using electron microscopy and uncovered a high degree of individual variation in SG structure. Our studies provide evidence for two alternative models for the origin of the salivary duct, the structure facilitating parasite transport out of SGs. We compare SG cellular architecture inAn. stephensi andDrosophila melanogaster, a fellow Dipteran whose adult SGs are nearly completely unstudied, and find many conserved features despite divergence in overall form and function.Anopheles salivary proteins previously observed at the basement membrane were localized either in SG cells, secretory cavities, or the SG lumen. Our studies also revealed a population of cells with characteristics consistent with regenerative cells, similar to muscle satellite cells or midgut regenerative cells. Conclusions This work serves as a foundation for linkingAnopheles stephensi SG cellular architecture to function and as a basis for generating and evaluating tools aimed at preventing malaria transmission at the level of mosquito SGs.